Aggregate distribution and substrate-induced respiration under different tillage and mulching management systems in organic farming. Issue 6 (1st November 2020) - Hashimi, Rahmatullah; Kaneda, Satoshi; Kaneko, Nobuhiro; Ohta, Hiroyuki; Komatsuzaki, Masakazu
ABSTRACT: In organic farming, intensive tillage for weed eliminating may cause physical and biological soil degradation. Weed residue mulch can be used to stabilize the organic carbon in the soil by improving soil aggregation and increasing microbial activity. However, the effectiveness of weed mulch in no-tillage (NT) and conventional tillage (CT) systems remains unclear. Therefore, we studied the influence of clipped weed mulch (CM) and no mulch (NM), in combination with NT and CT on the water-stable aggregates, and carbon stabilization in different-sized soil aggregates as well as on substrate-induced respiration (SIR) and the fungal-to-bacterial activity ratio at a soil depth of 0–5 cm. Macroaggregates (>4 mm water- stable aggregates) were 46.8% higher in NT than in CT in June and October 2014 and 52.4% higher with NT in 2015. Microaggregates (0.5- and 0.25-mm aggregates) were higher in CT than NT in both years. The use of CM also increased water-stable aggregates in both years. In 2014, >4-mm aggregate fraction was 6.5% higher with CM than with NM. In 2015, the same parameters were even more effective, with >4-mm and 2-mm aggregate fractions were 23.9% and 34.9% higher with CM respectively. MWD was higher in NT than in CT in both years and CM had slightly increased (but not significantly) this in October. In both years, soil organic carbon (SOC) and nitrogen were significantly higher in NT than in CT, and in October CM further increased these in both tillage systems. In both tillage systems, the highest amounts of SOC was measured in >4-mm aggregate fraction than microaggregates. In both years, microbial SIR was higher in NT than in CT. Further, research is needed to find out long term effect of weed residue mulch in these changes in both tillage systems.